Penile Papillomatosis Associated with Persistent Paraphimosis in a Horse - de Melo, Lídio Ricardo Bezerra; Padilha, Mayla de Lisbôa; de Souto, Erick Platiní Ferreira; Assis, Daniel de Medeiros; Alves, Rodrigo Cruz; Correia, Gabriel da Silva; Riet-Correa, Franklin; Dantas, Antônio Flávio Medeiros (Acta Scientiae Veterinariae, 2020)
Background: Papillomas are cutaneous neoplasms, also known as warts. They are usually benign and are caused by a papillomavirus. The development of papillomas in certain locations on the body may cause irreparable consequences. Paraphimosis is a urological emergency characterized by the inability of the penis to retract or the impossibility of retention inside the foreskin, causing local circulatory disorders and severe pain. However, the association between genital papillomas and the development of paraphimosis in horses has not been previously documented. The objective here is to describe the clinical and histopathological aspects of a case of penile papilloma associated with persistent paraphimosis in a horse. Case: A 15-year-old mixed-breed, 350 kg, horse presented nodular and crusted lesions, similar to warts, on the penis and foreskin, which progressed over at least six months. An incisional biopsy of one of the nodular lesions of the horse’s penis was performed. Tissue fragments were collected, packed in 10% buffered formaldehyde, and sent for histopathological evaluation to the Animal Pathology Laboratory of the University Veterinary Hospital of the Federal University of Campina Grande (UFCG), Campus de Patos, Paraíba. The biopsy resulted in a histopathological diagnosis of papilloma, and the horse was reevaluated. Due to the severity of the clinical case, it was referred to the HVU/UFCG Large Animal Medical and Surgical Clinic for surgical removal of the penis. The penectomy product was sent to the Animal Pathology Laboratory. Macroscopically, the penis fragment measured 18.0×10.5×6.0 cm in size, had an irregular surface, and presented with numerous multilobulated, reddish nodules on a sessile base, which were exophytic with projections having the appearance of a "cauliflower." The nodules extended from the foreskin and compromised from the base of the penis to the glans. When cut, the nodules were soft, yellowish-white, and had an uneven surface. In the histological evaluation, diffuse and marked hyperplasia of the keratinocytes in both the basal cell layer and spinous layer (acanthosis) was observed, often with formations of digitiform projections. The keratinocytes had multifocal areas of intercellular (spongiosis) and intracellular (balloon degeneration) edema. In the upper layers of the spinous stratum, cells with small, hyperchromatic and eccentric nuclei were seen, which were surrounded by a clear perinuclear halo (koilocytes). In the supra-adjacent stratum corneum, diffuse and moderate parakeratotic hyperkeratosis was observed. Immunohistochemistry showed strong brown immunostaining of the cytoplasm and keratinocyte nuclei by anti-papillomavirus antibodies. Discussion: The clinical manifestation of papillomas varies according to multiple factors, including the immune and nutritional status of the animal. Generally, papillomavirus infections are subclinical, unlike the present case. Due to the severity of the proliferation of papillomas, surgical amputation of the penis was necessary as a therapeutic measure. This type of intervention is considered uncommon or rare in cases of papillomatosis, as well as in the development of secondary paraphimosis. The permanent exposure of the penis resulted in discomfort, pain, inflammation, local infection, and self-mutilation, due to intense itching. Eventually, papillomas may be associated with the appearance of squamous cell carcinoma, a malignant tumor. In this case, the papilloma in the foreskin and penis triggered paraphimosis, with subsequent traumatic injuries to the glans and opportunistic infections that led to amputation of the organ.